Sulfur defect heterojunction molybdenum disulfide and light induction preparation method and application thereof
The preparation of sulfur-deficient heterojunction molybdenum disulfide under xenon light irradiation by light induction method has solved the preparation problem of high temperature and high energy consumption in the prior art, achieved efficient electrocatalytic hydrogen production performance, and simplified the preparation process.
Patent Information
- Application Number
- CN202411908155.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The prior art requires high temperature and high energy consumption when preparing sulfur vacant molybdenum disulfide catalysts, and the preparation process is complicated, making it difficult to achieve a gentle and rapid preparation method.
The sulfur-deficient heterojunction molybdenum disulfide was prepared by light induction. By using hydrogen to take away part of S in MoS2 under xenon light, S vacancy was formed, and in this process, part of the 1T crystal form MoS2 was converted into a 2H crystal form to form a heterojunction.
The rapid preparation of sulfur-deficient heterojunction molybdenum disulfide under low heat conditions was achieved, which significantly improved its electrocatalytic hydrogen production performance, simplified the preparation process, and reduced energy consumption.
Smart Images

Figure CN119710783A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a sulfur-deficient heterojunction molybdenum disulfide and a light-induced preparation method and application thereof. Background Art
[0002] In today's world, energy depletion, air pollution, greenhouse gas emissions and other problems have been plaguing humanity and have prompted humanity to explore and utilize clean and renewable energy. Among them, hydrogen energy is a clean, efficient, safe and sustainable new energy source; however, hydrogen energy is a secondary energy source, and hydrogen production technology has become one of the core issues in the utilization of hydrogen energy. Among the many hydrogen production technologies, electrochemical water decomposition technology (water decomposition into hydrogen and oxygen) has good development prospects, and the preparation of efficient catalysts for electrocatalytic hydrogen production (Hydrogen Evolution Reaction, HER) in the cathode part has become a key technology.
[0003] Molybdenum sulfide (MoS2) has the characteristics of high melting point and hardness, good thermal stability, mechanical stability and excellent corrosion resistance. It has been widely used in various fields such as high temperature resistance, friction resistance and chemical corrosion resistance. Its graphene-like structure and excellent physical and chemical properties are widely used in electrocatalytic hydrogen evolution research. At the same time, it also has electronic structure and catalytic properties similar to precious metals. It can be widely used as a catalyst for reactions involving hydrogen, such as alkane isomerization, unsaturated hydrocarbon hydrogenation, hydrodesulfurization and denitrogenation. It is comparable to precious metals platinum and iridium in catalysis. It is a very promising electrocatalyst and is called a "platinum-like catalyst."
[0004] The edge sites of MoS2 are its main active centers. These sites have a lower free energy barrier for hydrogen evolution reaction, which helps to improve the efficiency of HER. The electrocatalytic performance of MoS2 in HER is affected by many factors, including its morphology, crystal phase and defect structure. Li (ACS nano 13.6 (2019): 6824-6834.) et al. pointed out that sulfur vacancy defects in metal sulfides are the key to improving their HER performance. Sulfur vacancies can provide more active sites for the reaction and improve the electron transfer path, thereby significantly reducing the overpotential of the reaction and improving the catalytic activity.
[0005] At present, the preparation of S defects mainly relies on high-temperature thermal reduction and chemical reduction. For example, hydrogen is used as a reducing gas and S defects are produced by calcining at a high temperature of more than 600°C for 2 hours (ACS nano 13.6 (2019): 6824-6834.); However, this method requires high temperature and continuous introduction of hydrogen gas to prepare S defects, which consumes a lot of energy and takes a long time to react. The crystal phase transformation of the catalyst often requires high energy consumption to be achieved (Advanced Materials 32.33 (2020): 2001889.).
[0006] Therefore, how to gently and quickly prepare sulfur vacancy MoS2 materials remains to be explored. Summary of the invention
[0007] The present invention provides a sulfur-deficient heterojunction molybdenum disulfide and a light-induced preparation method and application thereof. The MoS2 prepared by the method contains a sulfur-vacancy synergistic crystalline phase heterojunction, which increases the reaction active sites and effectively improves the electrocatalytic hydrogen production performance of MoS2.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing sulfur-deficient heterojunction molybdenum disulfide by light induction, comprising:
[0010] S1. After the molybdenum source, sulfur source and deionized water are stirred evenly, they are transferred into a high-pressure reactor with a carbon cloth built in, and a carbon cloth with a MoS2 precursor uniformly grown is obtained by hydrothermal reaction;
[0011] S2. In a mixed atmosphere of hydrogen and inert gas, the carbon cloth uniformly grown with MoS2 precursor prepared in S1 is treated with xenon lamp light to obtain heterojunction molybdenum disulfide containing sulfur defects.
[0012] The present invention utilizes carbon cloth as a growth substrate of MoS2, and obtains a MoS2 precursor by a hydrothermal reaction. Further, utilizing the instability of the MoS2 precursor, hydrogen is used to take away part of the S in MoS2 under the illumination of a xenon lamp, and the taken-away part of the S leaves in the form of H2S gas, thereby forming S vacancies on MoS2. At the same time, under the illumination of a xenon lamp, due to electron escape, part of the 1T crystal form of MoS2 is transformed into a 2H crystal form, and the MoS2 generated at this time is actually a mixture of 1T crystal form MoS2 and 2H crystal form MoS2, and at the same time, these two different crystal forms of MoS2 form a heterojunction, and the final product obtained by the present invention is a heterojunction molybdenum disulfide (a heterojunction of 1T crystal form MoS2 and 2H crystal form MoS2) containing sulfur defects (S vacancies).
[0013] In addition, the sulfur-deficient heterojunction molybdenum disulfide obtained by the present invention showed a catalytic activity far stronger than that of single MoS2 in the electrocatalytic hydrogen production performance test.
[0014] It is worth noting that, generally, in order to create S vacancies in the MoS2 precursor by means of high temperature, calcination at a temperature above 600°C is required, which has a high requirement for heat. However, the xenon lamp irradiation method proposed in the present invention has a lower requirement for heat. The temperature on the surface of the MoS2 precursor is generally around 200°C. With the strong light absorption characteristics of the black powder of the MoS2 precursor, light energy is converted into heat energy on the powder surface, and defect manufacturing is completed with only relatively low heat.
[0015] Preferably, in S1, the temperature of the hydrothermal reaction is 180-220° C., and the time of the hydrothermal reaction is 18-24 h.
[0016] More preferably, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 18 h.
[0017] Preferably, in S1, the molybdenum source is ammonium molybdate or ammonium tetrathiomolybdate, and the sulfur source is thiourea, thioacetamide or L-cysteine.
[0018] More preferably, the molybdenum source is ammonium molybdate, and the sulfur source is thiourea.
[0019] Preferably, in S1, the carbon cloth is pre-washed with an organic solvent and naturally dried before being placed in a high-pressure reactor.
[0020] More preferably, the carbon cloth is washed with acetone, then washed with deionized water and anhydrous ethanol, dried naturally, and then transferred into a high-pressure reactor.
[0021] Preferably, in S2, the inert gas is argon and / or nitrogen.
[0022] More preferably, the inert gas is argon.
[0023] Preferably, in S2, the volume ratio of hydrogen to inert gas is 1:(6-9).
[0024] More preferably, the volume ratio of hydrogen to inert gas is 1:9.
[0025] Preferably, in S2, the current of the xenon lamp is 18-20A, the duration of the xenon lamp illumination is 10-20min, the intensity of the xenon lamp illumination is 3-13sun, 1sun≈100mW / cm 2 .
[0026] More preferably, the current of the xenon lamp is 18-19A, the duration of the xenon lamp illumination is 12-18min, and the intensity of the xenon lamp illumination is 5-10sun, 1sun≈100mW / cm 2 .
[0027] Further preferably, the current of the xenon lamp is 19A, the duration of the xenon lamp illumination is 15min, and the intensity of the xenon lamp illumination is 6sun, 1sun≈100mW / cm 2 .
[0028] The present invention also provides sulfur-deficient heterojunction molybdenum disulfide prepared by the method.
[0029] Preferably, the sulfur-deficient heterojunction molybdenum disulfide contains a heterojunction of IT-type molybdenum disulfide and 2H-type molybdenum disulfide.
[0030] The present invention also provides the sulfur-deficient heterojunction molybdenum disulfide prepared by the above method or the use of the above sulfur-deficient heterojunction molybdenum disulfide in electrocatalytic hydrogen production.
[0031] Therefore, the present invention has the following beneficial effects:
[0032] (1) The present invention proposes to prepare MoS2 with S vacancies by replacing high-temperature calcination with xenon lamp irradiation. The MoS2 prepared by this method is in the form of a heterojunction of two crystal forms, which can provide new ideas for subsequent research on crystal phase heterojunctions and related methods of creating defects with sulfides.
[0033] (2) The sulfur-deficient heterojunction molybdenum disulfide prepared by the present invention has S defects and also contains a heterojunction of IT-type molybdenum disulfide and 2H-type molybdenum disulfide, and exhibits ultra-high electrocatalytic hydrogen production activity.
[0034] (3) The method provided by the present invention greatly simplifies the preparation process of defect formation accompanied by crystal phase transformation represented by molybdenum sulfide. The entire production process does not require the use of precision instruments and has the characteristics of simple and easy synthesis operation and short reaction time (10 to 20 minutes).
[0035] (4) The method provided by the present invention does not require the introduction of expensive or dangerous gases such as ammonia and methane for a long time, thus overcoming the problem of long-term high-temperature operation of high-temperature furnaces in traditional methods, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of xenon lamp illumination of the present invention;
[0037] Figure 2 This is an EPR comparison chart;
[0038] Figure 3 is the XRD comparison chart;
[0039] Figure 4 This is a Raman comparison chart;
[0040] Figure 5 It is the XPS Mo 3d image;
[0041] Figure 6 This is the XPS S2p image;
[0042] Figure 7 This is the LSV evaluation data diagram of electrocatalytic hydrogen production under 1M KOH;
[0043] Figure 8 This is the LSV evaluation data diagram for electrocatalytic hydrogen production of 0.5M H2SO4. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0045] [Example]
[0046] Example 1
[0047] S1. The carbon cloth is cleaned with acetone, deionized water and anhydrous ethanol, and then dried naturally for later use.
[0048] S2. Accurately weigh 0.206 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and 0.3806g thiourea (CH4N2S) were dissolved in 30mL deionized water under magnetic stirring to form a uniform solution. The solution was then transferred to a 50mL Teflon-lined stainless steel autoclave, and the cleaned carbon cloth was immersed in the mixed solution as a growth substrate. The autoclave was placed in an electric furnace at 200°C, and after reacting for 18 hours, the reaction system was cooled to room temperature. The final product was washed several times with deionized water and anhydrous ethanol to remove any possible ions; it was naturally dried at room temperature to obtain a carbon cloth with uniformly grown MoS2. The carbon cloth on which MoS2 was grown was cut into pieces with a size of 0.5*1cm 2 The cut carbon cloth with MoS2 growth was irradiated with xenon lamp in H2 (10 vol% H2 and 90 vol% Ar mixed gas) atmosphere, the current of xenon lamp irradiation was 19A, the irradiation time was 15min, and the intensity of xenon lamp irradiation was 6sun. Sulfur defect heterojunction molybdenum disulfide material was obtained.
[0049] Comparative Example 1
[0050] This comparative example is basically the same as Example 1, except that the xenon lamp irradiation step is eliminated and the molybdenum disulfide material is obtained after hydrothermal treatment.
[0051] Comparative Example 2
[0052] This comparative example is basically the same as Example 1, except that the mixed gas of 10 vol% H2 and 90 vol% Ar is replaced by a pure argon atmosphere to obtain a molybdenum disulfide material.
[0053]
Performance test
[0054] 1. Vacancy
[0055] The catalyst materials prepared in Example 1 and Comparative Examples 1-2 were subjected to EPR testing to verify whether S vacancies occurred. The results are as follows: Figure 2 Observation Figure 2 It can be seen that no vacancy signal appears in Comparative Examples 1 and 2, while a strong vacancy signal appears in Example 1. This result indicates that only the catalytic material prepared in Example 1 has sulfur defects.
[0056] 2. Morphology and structure
[0057] In order to verify the EPR results and further analyze the material structure, the catalyst materials prepared in Example 1 and Comparative Examples 1-2 were subjected to XRD test, Raman test and XPS structure.
[0058] Figure 3 is the XRD pattern, where The mark corresponds to the 2H phase MoS2 standard card of JPDS No. 37-1492; the "∮" mark corresponds to the IT phase MoS2. It can be observed that the molybdenum disulfide material prepared in Comparative Example 1 is IT phase MoS2, and the molybdenum disulfide material prepared in Comparative Example 2 is 2H phase MoS2. Combining the results of EPR and XRD, it can be clearly inferred that the molybdenum disulfide material in Comparative Example 1 is a single phase IT phase MoS2 and does not contain sulfur defects, while the molybdenum disulfide material in Comparative Example 2 is a single phase 2H phase MoS2 and does not contain sulfur defects. The spectrum corresponding to Example 1 shows two phases, IT phase and 2H phase, and it is speculated that sulfur-defective molybdenum disulfide with a mixed-phase heterojunction structure may have been formed.
[0059] Figure 4 The Raman spectrum of Comparative Example 1 is at 151.4 cm -1 、233.1cm -1 and 345.8cm -1 The peaks at 280 cm correspond to the J1, J2 and J3 bands of 1T phase MoS2; -1 The peak at corresponds to E1g , indicating the octahedral coordination in 1T-MoS2. The Raman peak of comparative example 2 only appears at 377 cm -1 and 403cm -1 The two peaks correspond to the E 1 2g and A 1g The Raman peaks of Example 1 not only show the typical J1, J2 and J3 band peaks of 1T phase MoS2, but also the typical E band peaks of 2H-MoS2. 1 2g and A 1g This result verifies the existence of 1T-MoS2 and 2H-MoS2 heterojunction.
[0060] Figure 5 and Figure 6 The XPS graphs of the catalyst materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 5 It can be seen that the two peaks of 229eV and 232.3eV in Comparative Example 1 correspond to Mo on 1T-MoS2, respectively. 4+ 3D 5 / 2 and 3D 3 / 2 The two peaks at 229.9 eV and 232.9 eV in Comparative Example 2 correspond to 2H-MoS2 Mo 4+ 3D 5 / 2 and 3D 3 / 2 In Example 1, characteristic peaks corresponding to 1T-MoS2 and 2H-MoS2 appeared.
[0061] Figure 6 The S2p spectra of Example 1, Comparative Example 1 and Comparative Example 2 are similar. 2- 2p 1 / 2 The peak shifts toward higher energy; from 162.1 eV in Comparative Example 1 to 163.1 eV in Comparative Example 2.
[0062] The conclusion of XPS once again confirms that the 1T and 2H phases of MoS2 coexist in Example 1. Combining the results of XRD, Raman and XPS, it can be determined that the structure of Example 1 is a mixed-phase heterojunction structure with sulfur defects.
[0063] 3. Electrocatalytic hydrogen production
[0064] Catalytic performance test method:
[0065] ① Linear sweep voltammetry (LSV) scanning was performed using a CHI660D electrochemical workstation with the following parameters: Init E = -0.159 V, Final E = 0.659 V, Scan Rate = 0.005 V / s, Sample Interval = 0.001 V, Quiet Time = 2, Sensitivity = 1.e-002 A / V. The electrolyte was 0.5 M sulfuric acid solution, and a saturated calomel electrode (SCE) and a carbon rod were used as the reference electrode and counter electrode, respectively.
[0066] ② Linear sweep voltammetry (LSV) scanning was performed using a CHI660D electrochemical workstation with the following parameters: Init E = -0.784 V, Final E = -1.684 V, Scan Rate = 0.005 V / s, Sample Interval = 0.001 V, Quiet Time = 2, Sensitivity = 1.e-002 A / V. The electrolyte was 1 M potassium hydroxide solution, and a saturated calomel electrode (SCE) and a carbon rod were used as the reference electrode and counter electrode, respectively.
[0067] The catalyst materials prepared in Example 1 and Comparative Examples 1-2 were tested for electrocatalytic hydrogen production. The results are as follows: Figures 7-8 In order to confirm the effect of Xe light induced S vacancy cooperative crystalline phase heterojunction on the electrocatalytic performance, LSV was carried out in alkaline and acidic media to evaluate the HER performance of the catalyst.
[0068] LSV was performed in 1 M KOH to evaluate the HER activity of the catalysts, and the results are shown in Figure 7 shown. Figure 7 When the current density is fixed at 10 mA cm -2 When the overpotential of the 1T phase MoS2 obtained in comparative example 1 is 253mV, the overpotential of the 2H phase MoS2 obtained in comparative example 2 is 192mV, and the overpotential of the sulfur-defect heterojunction molybdenum disulfide material obtained in embodiment 1 is 155mV. Analysis shows that the catalytic material containing 2H phase MoS2 has a lower overpotential than that of 1T phase MoS2, which indicates that the 2H phase MoS2 has a greater impact on the HER performance. Among them, the overpotential of the sulfur-defect heterojunction molybdenum disulfide material is significantly lower than that of the single-phase MoS2 material without sulfur defects, which indicates that the formation of S vacancy cooperative crystalline phase heterojunction induced by xenon lamp illumination will produce more active sites, thereby improving the HER performance of MoS2 materials in alkaline media.
[0069] observe Figure 8It can be seen that the overpotentials of the catalyst materials obtained in Comparative Example 1 and Example 1 are 232 mV and 192 mV respectively; at the same time, it can be found that the overpotentials are ranked from small to large as follows: Example 1, Comparative Example 2, Comparative Example 1. These results prove that the S vacancy synergistic crystalline phase heterojunction significantly improves the HER activity of MoS2 materials in acidic (0.5M H2SO4) media, and the performance is similar to the HER performance results of the S vacancy synergistic crystalline phase heterojunction in alkaline media.
Claims
1. A method for preparing sulfur-deficient heterojunction molybdenum disulfide by light induction, characterized in that: include: S1. After the molybdenum source, sulfur source and deionized water are stirred evenly, they are transferred into a high-pressure reactor with a carbon cloth built in, and a carbon cloth with a MoS2 precursor uniformly grown is obtained by hydrothermal reaction; S2. In a mixed atmosphere of hydrogen and inert gas, the carbon cloth uniformly grown with MoS2 precursor prepared in S1 is treated with xenon lamp light to obtain heterojunction molybdenum disulfide containing sulfur defects.
2. The method according to claim 1, characterized in that In S1, the temperature of the hydrothermal reaction is 180-220° C., and the time of the hydrothermal reaction is 18-24 hours.
3. The method according to claim 1 or 2, characterized in that In S1, the molybdenum source is ammonium molybdate or ammonium tetrathiomolybdate, and the sulfur source is thiourea, thioacetamide or L-cysteine.
4. The method according to claim 1, characterized in that In S1, the carbon cloth is preliminarily washed with an organic solvent and naturally dried before being placed in a high-pressure reactor.
5. The method according to claim 1, characterized in that In S2, the inert gas is argon and / or nitrogen.
6. The method according to claim 1 or 5, characterized in that In the S2, the volume ratio of hydrogen to inert gas is 1:(6-9).
7. The method according to claim 1, characterized in that In S2, the current of the xenon lamp is 18-20A, the time of the xenon lamp illumination is 10-20min, the intensity of the xenon lamp illumination is 3-13sun, 1sun≈100mW / cm 2 .
8. Sulfur-deficient heterojunction molybdenum disulfide prepared by the method according to any one of claims 1 to 7.
9. The sulfur-deficient heterojunction molybdenum disulfide according to claim 8, characterized in that: The sulfur-deficient heterojunction molybdenum disulfide contains a heterojunction of IT-type molybdenum disulfide and 2H-type molybdenum disulfide.
10. Use of the sulfur-deficient heterojunction molybdenum disulfide prepared by the method according to any one of claims 1 to 7 or the sulfur-deficient heterojunction molybdenum disulfide according to claim 8 or 9 in electrocatalytic hydrogen production.
Citation Information
Patent Citations
Preparation method for MoS2 / CC (molybdenum disulfide / carbon cloth) composite hydrogen evolution electro-catalytic material
CN107442138A
Nitrogen-doped defect-rich molybdenum disulfide catalyst as well as preparation method and application thereof
CN113178584A
Molybdenum disulfide catalyst with adjustable phase composition and large interlayer spacing as well as preparation method and application of molybdenum disulfide catalyst
CN114507875A
Sulfur-vacancy-rich nickel sulfide nanosheet array structure catalyst material as well as preparation method and application thereof
CN115233250A
MoS2 self-standing catalytic hydrogen evolution electrode with defect introduced by cold plasma as well as preparation method and application of MoS2 self-standing catalytic hydrogen evolution electrode
CN115725998A